A systematic approach for horizontal and vertical scale up of sintered Ultra-High Temperature Ceramic Matrix Composites for aerospace – Advances and perspectives. (1st April 2022) - Sciti, D.; Zoli, L.; Reimer, T.; Vinci, A.; Galizia, P.
Abstract: Ultra-High Temperature Ceramic Matrix Composites (UHTCMCs) are the next generation composites developed for application in the harsh environment of aerospace. Qualification of these materials requires the manufacturing of demonstrators for testing in relevant environments, which in turn, requires to scale them up. This paper illustrates the systematic approach adopted for the scale-up of UHTCMCs based on carbon fibre reinforced zirconium diboride plus silicon carbide from laboratory to industrial scale dimensions. The scale-up process covered a period of three years and concerned an increase in diameter of ∼10 times (from 40 to 400 mm), and in thickness of ∼30 times (from 5 to 160 mm). Small-scale products were consolidated by hot pressing at ISTEC whilst larger samples were consolidated by an industrial spark plasma sintering facility (NanokerResearch, Spain). After each scale-up step, reproducibility of composition, microstructure and properties was carefully checked. Thanks to the homogenous fibre distribution and sapient dosing of secondary phases, composites with different diameters and thickness were successfully consolidated by both techniques with little adjustment of sintering parameters up to the maximum size of available industrial furnaces. The large discs produced allowed production of 170 mm long bars for tensile testing and large tiles for hypersonic wind tunnel tests. Thick samples were useful to machine complex shapes such as screws and nuts, vertical bars for characterization of properties along the composite thickness and nozzle demonstrators. Graphical abstract: Image 1 Highlights: ZrB2 -Cf composites were scaled-up 10 times in diameter, 30 times in thickness. A manufact of UHTCMC material weighting 11 kg was produced for the first time. The same mechanisms were efficient for scale-up in diameter and thickness. Reproducible microstructure-properties were assessed from lab to industrial scale. Large components such as plates, nozzle inserts, screw and nuts were fabricated.